2014
DOI: 10.9790/0853-1392122127
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Haematological Parameters among Pregnant Women Attending Antenatal Clinic in College Of Health Demonstration Clinic, Port Harcourt

Abstract: This research evaluated the haematological parameters of pregnant women in college of health demonstration clinic, Port Harcourt, Nigeria. The results indicated an elevation in WBC concentration of pregnant women when compared with that of apparently non pregnant women while PCV concentration of pregnant women decreased significantly when compared with that of apparently non pregnant women. This result also indicated that some of the pregnant women were anemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
(4 reference statements)
0
2
1
Order By: Relevance
“…RBCs count was significantly higher in the first trimester compared with the third (4.68 ± 0.52 versus 4.48 ± 0.71, P < 0.01) but changes in Hgb and Hct values were not significant between all the trimesters. This finding did not agree with the findings obtained in studies conducted in Port Harcourt and Nigeria, where Hct values significantly decreased as gestational age increases [ 1 , 28 ]. A study conducted in Nigeria indicated that most RBC indices were significantly changed across trimesters [ 11 ].…”
Section: Main Textcontrasting
confidence: 94%
“…RBCs count was significantly higher in the first trimester compared with the third (4.68 ± 0.52 versus 4.48 ± 0.71, P < 0.01) but changes in Hgb and Hct values were not significant between all the trimesters. This finding did not agree with the findings obtained in studies conducted in Port Harcourt and Nigeria, where Hct values significantly decreased as gestational age increases [ 1 , 28 ]. A study conducted in Nigeria indicated that most RBC indices were significantly changed across trimesters [ 11 ].…”
Section: Main Textcontrasting
confidence: 94%
“…In spite of this, global reports in 2017 showed that only three in five women attended at least four antenatal visits. In regions with the highest rates of maternal mortality, such as SSA, only 52% of women received at least four ANC visits [12][13][14]. ANC promotes the health of pregnant women and has been found to reduce the risk of adverse pregnancy outcomes, perinatal and infant mortality and morbidity [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In Uganda according to the Uganda Demographic Health Survey in 2016 the antenatal coverage was at 60% for at least four antenatal care visits throughout the pregnancy period [9]. Reduction in the death of mothers due to pregnancy and pregnancy-related conditions is the core aim of antenatal care globally [10,11]. More so, antenatal care also reduces the incidence of mother-tochild transmission of HIV (MTCT).…”
Section: Introductionmentioning
confidence: 99%